Non-State Actor Contribution in Achieving Sustainable Development Goals: Capturing Global Reporting Initiative Role in Indonesia - Kurniawan, Andrian Dwi; Nur, Asrul Ibrahim (Andalas Journal of International Studies (AJIS), 2022)
This study analysed and discussed non-state actors' role in achieving Sustainable Development Goals (SDGs) in Indonesia. The focus of the study is the Global Reporting Initiative (GRI), one of the NGOs widely recognised as a provider of sustainability reporting standards. This study adopted qualitative research methods by collecting data from literature studies and interview competent informants from GRI Indonesia representatives, related industries, expert academics, and government representativies Furthermore, the data were analysed using triangulation methods to answer research questions adequately. The findings of this study show that GRI has a significant role in achieving the SDGs in Indonesia. GRI uses a pattern of collaboration and cooperation and provides sustainability-related training in promoting the use of GRI Standards to both regulators and companies. The results of this study are expected to provide the latest discourse on the role of non-state actors in achieving SDGs as the global commitment of countries in the world.